2015
DOI: 10.2466/01.pr0.116k26w0
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Dimensionality of Colquitt's Organizational Justice Scale in a Public Health Sector Context

Abstract: In 2001, Colquitt developed an Organizational Justice Scale that intended to measure procedural, distributive, interpersonal, and informational justice. The dimensionality of the scale has been tested in subsequent studies with diverging results. Given the fact that contextual differences may account for more variation across research sites than individual differences, the deviating research findings may be due to context. This study examined the dimensionality of Colquitt's Organizational Justice Scale in a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The results obtained conclude that the structure of four organizational justice factors (distributive, procedural, interpersonal and informative) are concordant as in other studies carried out in different countries, according to the studies carried out (Colquitt, 2001;Díaz-García et al, 2014;Enoksen, 2015;Olsen et al, 2012;Omar et al, 2003;Streicher et al, 2008). This finding contributes to the existing body of knowledge about the structure of the organizational justice scale of Colquitt, as well as to the conception of organizational justice as a four-factor construct (distributive, procedural, interpersonal and informative).…”
Section: Conclusion and Some Policy Implicationssupporting
confidence: 86%
“…The results obtained conclude that the structure of four organizational justice factors (distributive, procedural, interpersonal and informative) are concordant as in other studies carried out in different countries, according to the studies carried out (Colquitt, 2001;Díaz-García et al, 2014;Enoksen, 2015;Olsen et al, 2012;Omar et al, 2003;Streicher et al, 2008). This finding contributes to the existing body of knowledge about the structure of the organizational justice scale of Colquitt, as well as to the conception of organizational justice as a four-factor construct (distributive, procedural, interpersonal and informative).…”
Section: Conclusion and Some Policy Implicationssupporting
confidence: 86%
“…As an organization‐level resource, work environment is assumed to be an extrinsic motivator of work engagement in the JD‐R model and has often been examined in empirical studies. However, in such research investigators have mostly focused on the nursing‐specialized practice environment and less on organizational justice in healthcare organizations (Enoksen, ). In this study, we found that the two dimensions of distributive justice and informational justice had positive associations with work engagement, with informational justice being the strongest explanatory variable in model 2 (see Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Informational justice is defined as the perceived fairness of information and explanations about procedures and outcomes in the organization. Timely and reasonable explanation and transparency of information enhance the feeling of fairness and meet the needs of respect (Enoksen, ). Therefore, nurses are likely to experience low levels of work engagement when they perceive that the organization treats them unfairly in terms of distributive outcomes and distributive information.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational justice was measured by using the fifteen-item scale of justice validated by Enoksen (2015). A five-point Likert scale was used to analyze the respondents' level of agreement.…”
Section: Organizational Justicementioning
confidence: 99%